Modulation of human lymphocyte proliferation by salivary gland extracts of ixodid ticks (Acari: Ixodidae): effect of feeding stage and sex - Rolníková, Terézia; Kazimírová, Mária; Buc, Milan (Folia parasitologica, 2003)
Ixodid ticks remain attached to their hosts for several days to weeks. During this extended feeding process new proteins involved in the modulation of host immune responses are expressed in tick salivary glands. In our study a stimulatory or inhibitory effect of salivary gland extracts (SGE) of unfed and partially fed female Ixodes ricinus (Linnaeus, 1758), female and male Amblyomma variegatum (Fabricius, 1794) and Rhipicephalus appendiculatus Neumann, 1901 ticks on human lymphocyte proliferation induced by Concanavalin A (ConA) and phytohaemagglutinin (PHA), respectively, was investigated. SGE of all female ticks examined suppressed proliferation of ConA-induced lymphocytes; highly significant suppression was observed in the presence of unfed I. ricinus and 9-day fed A. variegatum SGE. SGE of partially fed A. variegatum and I. ricinus females suppressed PHA responses of lymphocytes. Lymphocytes showed reduced PHA and ConA responses in the presence of SGE of unfed and 2-day fed R. appendiculatus females, while SGE of 6-day fed females enhanced PHA responses, but reduced their ConA responses; generally SGE of 2-day fed females displayed the strongest inhibition. Amblyomma variegatum male SGE slightly enhanced PHA, but significantly reduced ConA responses of lymphocytes and their inhibitory effect increased during feeding. SGE of unfed and 2-day fed R. appendiculatus males enhanced PHA and ConA responses and those of 6-day fed males suppressed lymphocyte proliferation. The results suggest that (i) species- and sex-specific differences exist in the effects of tick salivary gland antigens on human lymphocyte proliferation and (ii) effect of SGE on human lymphocyte responses to mitogens varies depending on the tick feeding status.
Keywords: Animals; Tissue Extracts; Female; slinné žlázy; Salivary Glands; ženské pohlaví; druhová specificita; stravovací zvyklosti; Lymphocyte Activation; aktivace lymfocytů; lidé; Species Specificity; Ixodidae; Sex Characteristics; Male; Feeding Behavior; pohlavní dimorfismus; tkáňové extrakty; zvířata; mužské pohlaví; Humans